STRESS-STRAIN STATE MODELING OF THE PRECAST CONCRETE SLABS, COMPOSED OF THE DISK OVERLAP - , Е. Г., А. В. (Municipal economy of cities. Series: «Economy science», 2016)
We offer to construct flooring from reinforced concrete precast hollow slabs that ensures structural design of several slabs within floor slab instead of convenient beam-type structural design of separate slab within the flooring. Thus, we have quasi-contour design of operation of flooring slab. Flooring, consisting of several beam slabs within flooring cell in question, has finite bending stiffness in longitudinal direction that depends on geometrical and physical-mechanical parameters and also reinforcement of each separate slab. In transverse direction composite flooring slab has almost zero bending stiffness and bears load due to shear rigidity of the joint and torsion resistance of each slab. This arrangement reduces loads, applied to flooring slab. Represented results of calculations and their comparison by analytical and numerical methods (FEM). Keywords: stress-strain state, modeling, efficiency ratio, rate reduction, flexural stiffness, torsional rigidity, FEM.